(untitled) (Journal of Human Sciences, 2023)
The study deals with the impact of climate on the water budget to determine the water surplus or shortage in northwestern Libya. The study relies on climate data for seven meteorological stations for the period (1971-2010). The potential water losses are estimated by the equations of Ivanov and Khosella, and then finding the difference between the rainfall averages and the water losses rates to estimate the water shortage. GIS is used to determine the spatial distribution of the water balance in the study area. The study shows that the potential evapo-transpiration tend to be significantly high in most parts of the study area compared to precipitation rates, Hence, the water shortage exists at the majority of the study area except of Gharyan station which has water surplus during the winter season only. Moreover, the amounts of water shortage are increasing toward the south direction to reach their highest averages in Ghadames.